2006
DOI: 10.29309/tpmj/2006.13.02.5007
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovarian Disease

Abstract: Introduction: Poly Cystic Ovarian Disease (PCOD) is probably one of the most commonendocrinological disorders amongst the women during their reproductive years. Using USG criteria only 20-33% ofapparently healthy women in childbearing period, have been found to have PCOD in population study. Whereasprevalence of 4-10% in women of reproductive age is commonly reported when the diagnosis is based on clinical,biochemical and US scan features. Objective:-Diagnosis and management of polycystic ovarian disease. Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In the present study, LH levels were elevated in more than 50% of participants, compared to 40% in Balen et al and 72% in the Multan study. 9,14 Prolactin was slightly raised in 3% of patients compared to 8% in the study at Multan. 14 In a study by Aziz et al in 2001 proportion of obese patients was also 30%.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…In the present study, LH levels were elevated in more than 50% of participants, compared to 40% in Balen et al and 72% in the Multan study. 9,14 Prolactin was slightly raised in 3% of patients compared to 8% in the study at Multan. 14 In a study by Aziz et al in 2001 proportion of obese patients was also 30%.…”
Section: Resultsmentioning
confidence: 54%
“…9,14 Prolactin was slightly raised in 3% of patients compared to 8% in the study at Multan. 14 In a study by Aziz et al in 2001 proportion of obese patients was also 30%. 16 Another research done in Rawalpindi found that 58% of patients had elevated HDL levels, whereas 12% and 21% of patients had elevated cholesterol and triglyceride thresholds.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation